Chemokine alterations in the postmortem brains of suicide completers. (January 2020) - Shinko, Yutaka; Otsuka, Ikuo; Okazaki, Satoshi; Horai, Tadasu; Boku, Shuken; Takahashi, Motonori; Ueno, Yasuhiro; Sora, Ichiro; Hishimoto, Akitoyo
Abstract: Suicide is a major health problem in the modern world. However, its physiological mechanisms have not been well elucidated yet. Immunological disturbances have been reported in psychiatric disorders such as major depressive disorder (MDD), bipolar disorder (BP), and schizophrenia. Some studies have also suggested an association between immunological alterations especially neuroinflammation, and suicide. Chemokines play important roles in inflammation, and studies investigating chemokines in psychiatric diseases such as schizophrenia, MDD, and BP have reported chemokine dysregulations. However, there have been very few studies on the association between chemokines and suicide. We studied chemokine alterations in the postmortem brains of suicide completers and compared them to those of controls. We obtained brain tissue samples of the dorsolateral prefrontal cortex from 16 suicide completers and 23 controls. We examined the concentrations of chemokines and related substances in the brain tissue from these two groups using the Bio-Plex Pro™ Human Chemokine Panel 40-Plex. We performed multiple regression analysis with covariates. The levels of CCL1, CCL8, CCL13, CCL15, CCL17, CCL19, CCL20, CXCL11, and IL-10 were significantly decreased, whereas the IL-16 levels were significantly increased in the suicide completers after adjustment with the Benjamini-Hochberg method to control for type Ⅰ errors ( Q < 0.05). The observed chemokine alterations might suggest the presence of suicide-specific immunological mechanisms.